Comparison of Visual and Refractive Outcome between Two Methods of Corneal Marking for Toric Implantable Collamer Lenses (TICL) in Phakic Eyes - Feldhaus, Lukas; Mayer, Wolfgang J.; Dirisamer, Martin; Kassumeh, Stefan; Shajari, Mehdi; Priglinger, Siegfried G.; Luft, Nikolaus (Current Eye Research, 2023)
To compare the efficacy of digital-assisted reference marking for toric implantable collamer lenses (Callisto Eye System) with manual marking technique using a slit lamp markeur. This study included patients that underwent implantation of a toric implantable collamer lens (EVO Visian toric ICL, Staar Surgical). Patients were included if they had a myopia above −3 diopters (D) and regular corneal astigmatism of 0.75 diopters or higher. Between both groups a 1:2 matching regarding similar preoperative level of myopia and astigmatism was performed. Visual and refractive outcomes were evaluated. Vector analysis was performed to evaluate total astigmatic changes. This study comprised 57 eyes of 57 patients with 19 eyes in the digital group and 38 eyes in the manual marking group. Postoperatively there were no statistically significant differences between both groups in UDVA (p = 0.467), spherical equivalent (SE) (p = 0.864), sphere (p = 0.761) and cylinder (p = 0.878). Vector analysis showed a slightly more accurate postoperative refractive astigmatism in the manual group (0.26 D at 107° ± 0.50 D) compared to the digital marking group (0.31 D at 107° ± 0.45 D), nevertheless with no statistically significant differences between both groups. A digital tracking approach for toric ICL alignment was an efficient and safe method for toric marking with similar results regarding visual and refractive outcomes compared to a conventional corneal marking method. Nevertheless, image-guided surgery helped to streamline the workflow in refractive ICL surgery.